1972
DOI: 10.1007/bf01438410
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ionization on heat transfer to wires immersed in a highly thermallyionized plasma

Abstract: Results obtained with a previously developed technique for measuring local heat transfer to bare and ceramic coated metal wires from a dense, highly thermallyionized plasma are presented and compared with theoretical predictions. A free-burning arc in argon at atmospheric pressure provides a plasma in local thermodynamic equilibrium. Wire probes are swept through this plasma in planes parallel to the anode. The wires do not draw a net current from the plasma. Experimental evidence indicates that the layer betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
3
0

Year Published

1973
1973
1976
1976

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…4 are due to the variance in the inversion technique. Circumferentially averaged heat fluxes are about 60 watt/ram 2 in the center, in excellent agreement with data of [2,3,4]. Since Petrie [2] was unable to obtain satisfactory measurements with coated wires, this comparison refers only to bare metal surfaces.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…4 are due to the variance in the inversion technique. Circumferentially averaged heat fluxes are about 60 watt/ram 2 in the center, in excellent agreement with data of [2,3,4]. Since Petrie [2] was unable to obtain satisfactory measurements with coated wires, this comparison refers only to bare metal surfaces.…”
Section: Resultssupporting
confidence: 70%
“…Previous heat transfer studies in similar situations have been reported by Kimura and Kanzawa [1], Petrie [2], and Petrie and Pfender [3,4]. These authors measure the heat flow to cylindrical bodies immersed into an arc plasma.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…This was observed by Chludzinski et al (1965), Kimura andKanzawa (1965), andPetrie (1969). The argon plasma tail flames used in this work, however, reached only about 8 000°K.…”
Section: Pure Heat Transfersupporting
confidence: 61%
“…In order to calculate mean film temperatures, the particle surface temperature was required. This was calculated using the Ranz-Marshall ( 1952) correlation corrected for nonisothermal effects (Ahmed, 1967), ionization effects (Petrie, 1969), and recombination effects (Chludzinski, 1964). The latter correction was necessary due to the entrainment of considerable quantities of air by the hot argon jet.…”
Section: ( N P / D T ) = (-314) ( P S / P P ) { ( C D ) N I / D P > Imentioning
confidence: 99%